Pelaksanaan Pembelajaran Menulis Slogan Dan Poster Di SMP N 3 Kebakkramat - YULIYANTO, RAHMANDA EKO, Laili Etika Rahmawati, S.Pd., M.Pd (2017)
Learning to write slogans and posters is very important for students, through the learning of students can pour their creative ideas at once convey his ideas through messages in slogans and posters. This study to describe the implementation of the teaching of writing a slogan / poster SMP N 3 Kebakkramat. This study included into qualitative descriptive type. The data used in this study is Learning Implementation Plan (RPP), photo documentation of learning and student assignments in the form of writing a slogans and posters. Data collection techniques used in this research is interview, documentation, and direct observation. The result of this research is the analysis of Learning Implementation Plan, analysis of the implementation of learning by teachers and that teachers use assessment for learning. Keywords: writing, learning, slogans, posters.